Consumers' motivations to engage with local brands on social media - Esterhuyzen, Lisa (Stellenbosch University, 2024)
The 'consumer brand engagement' (CBE) concept comprehensively reflects consumers' motives for social media use, particularly digital consumer engagement behaviour. However, despite the growing scholarly interest in addressing 'engagement', disagreement exists regarding the nature of engagement behaviours and the predictive role of consumer motivations. Further, although there is a ‘buy local’ movement whereby consumers are encouraged to support local brands, the role of ethnocentrism in consumers’ decision to engage with local brands on social media has not been examined. To address these gaps in the literature, this study drew from the Uses and Gratifications Theory to examine CBE on social media in a local South African wine brand context and the possible moderating effects of ethnocentrism. A sequential mixed-method research design comprised of a qualitative phase one (focus group discussions) and a quantitative phase two (survey questionnaire) was utilised. The data recorded from phase one was thematically analysed, whereas Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed during phase two. Findings from phase one suggested that the concept of ‘local brand’ is contextual and that although consumers hold positive sentiments towards phrases such as ‘local is lekker’, an overall negative perception of South African product quality persists. Results from phase two revealed that consumer motivations to engage on social media predict consumer online brand-related activities (COBRAs) in varying degrees and that consumer ethnocentrism plays a limited moderating role. Theoretically, this study contributes by refining the model proposed by Buzeta et al. (2020), thus providing insight into the interrelationships that exist between consumers’ motives to engage with local wine brands on social media and their subsequent COBRAs. Managerially, brand managers need to understand that different motivations are associated with different COBRAs and adjust their social media campaigns accordingly.